“中文+职业教育”融合发展趋势——基于CiteSpace可视化分析 - Yue Hoong Leong (Sinolingua: Journal of Chinese Studies, 2025)
Since the launch of the “Belt and Road” Initiative, the integration of Chinese language and vocational education has become increasingly important in promoting cross-cultural communication and international industrial cooperation. To comprehensively identify research hotspots and trace the evolution of this field, this study analyzes 319 relevant articles from the China National Knowledge Infrastructure (CNKI) using CiteSpace 6.4.R1 for visualized bibliometric analysis. It examines dimensions including annual publication trends, core cluster groups, and burst keywords to map the developmental trajectory and research focus of “Chinese + Vocational Education.” The findings reveal four distinct stages of development: emergence, slow growth, rapid expansion, and peak adjustment. These stages are accompanied by a thematic shift from policy advocacy and conceptual exploration to textbook development, teacher training, cross-border collaboration, and digital resource construction. Cluster analysis shows that current hotspots center on the integration of vocational Chinese teaching and technology, internationalization of teaching models, regional cooperation practices, and the construction of teaching resources, while burst keyword analysis highlights emerging interests in artificial intelligence, instructional design, and cross-cultural adaptation. Despite growing attention, most studies remain case-oriented, with limited cross-regional comparison and long-term empirical evaluation. Future studies should reinforce comparative and evidence-based approaches, broaden interdisciplinary perspectives, and establish evaluative frameworks with broader applicability. The study concludes by proposing future directions for talent cultivation, emphasizing that the Content and Language Integrated Learning (CLIL) approach offers a viable pathway to developing interdisciplinary, cross-domain professionals.